Brief report on coca - Hinostroza García, Lauro (1985)
This report is part of the research led by Dr. Juan Ossio, commissioned by the Organization of American States (OAS) on "SOCIAL, CULTURAL, MEDICAL, AND ECONOMIC EFFECTS OF THE TRADITIONAL USE OF COCA IN POPULATIONS OF THE PATEAU AND HIGHLANDS OF PERU, ESPECIALLY OF INDIGENOUS PEOPLES ”. It exposes topics about the coca leaf in the Andean culture: classification criteria, myths, songs and a sample of qatipay or seguimiento. The latter is an important ritual practice for the Andean peasantry, it guides the present, past and future of all its activity. Each leaf, due to its shape, position and size, will reveal the social roles it has to assume, that is, the mysteries of time.